G55(P) Antiphospholipid syndrome should be considered as a possible causative factor in stroke in children with down's syndrome. (25th October 2020) - Bhatt, R; Ramdas, S
Abstract : Method: A three year old girl with Down's syndrome presented to her local DGH with a dense right sided hemiparesis and impaired speech. MRI brain showed an acute left MCA territory stroke with possible multiple events and vascular imaging (MRA) was suggestive of carotid dissection. The time of onset of her symptoms was unclear as she had been unwell with gastroenteritis the previous few days; therefore she was not a suitable candidate for thrombolysis. Investigations done as part of the RCPCH stroke guideline identified positive antibodies to beta2-glycoprotein and cardiolipin raising the possibility of antiphospholipid syndrome. She was initiated on low molecular weight heparin, repeat anticardiolipin and beta2-glycoprotein at three months remained elevated therefore confirming the diagnosis of antiphospholipid syndrome. Result: It is well recognized that patients with Down's syndrome are predisposed to autoimmune conditions, however the association with antiphospholipid syndrome is lesser well known and documented. There are four previous cases reported in literature, but only two children aged 6 years and 11 months at the time of the thrombotic event. This case report highlights the importance of thinking laterally and considering dual pathology as a possibility in particular when a clear history is not available regarding onset of symptoms. Despite initial investigations clearly providing an aetiology for the stoke i.e. carotid artery dissection in our case, it was imperative to not cease at this point in the diagnostic process. Antiphospholipid syndrome is a lifelong condition requiring long term anticoagulation treatment in order to prevent the debilitating impact of recurrent thromboembolic events such as stroke, DVT and recurrent miscarriages later in life. Therefore, early recognition of this condition in Down's syndrome patients who present with stroke may have the potential to prevent life-long disability.